Falta de aplicación del principio de proporcionalidad en la determinación de penas por delitos de tráfico, de sustancias estupefacientes y psicotrópicas. - Carrillo Armijos, Pascuala Liduvina (2014)
In this thesis is reflected in our interest to contribute in the best way, the establishment of a proper determination of sanctions in the case related to drug trafficking offenses, so that its implementation is proportionate to the crime committed and allow correct the serious violations of the rights of citizens, based on the legal regulations governing the legal life of the country, as is the Constitution of the Republic, international treaties and human rights conventions signed by Ecuador, criminal laws and other decrees and regulations existing thereon. Criminal laws have changed significantly, so it is not possible to continue administering justice under the decision of a judge or court of criminal guarantees and what his opinion considers sound criticism, ignoring repeatedly, the laws, doctrine and jurisprudence. We must not forget that this is life and liberty of a human being and therefore the penalty to be applied, shall correspond to the accumulation of evidence to enable judges to conclude unequivocally that the defendant has direct responsibility for the crime under investigation.